Krycklan Catchment Study - Unit for Field-based Forest Research, The Swedish University of Agricultural Sciences (Swedish University of Agricultural Sciences, 2019)
The Krycklan Catchment Study (KCS) is one of the most ambitious projects which integrate water quality, hydrology and aquatic ecology in running waters in the boreal region. KCS provide data services and high quality field data to allow state-of-the-art research in hydrological, biogeochemical and ecological processes. KCS aim to do basic science, develop new generations of water management models and provide background information for improved environmental guidelines.

Forskning inom Krycklans avrinningsområde integrerar mark- och akvatiska system och fokuserar främst på små vattendrags olika biogeokemiska sammansättning och motståndskraft mot förändringar.

Krycklan är ett 6 780 hektar stort avrinningsområde och utgör ett biflöde till Vindelälven, vilken startar i fjällen i väst och rinner ut i Östersjön i Umeå i öst. Bäcksystemet i Krycklan avvattnar i första hand brukade skogsområden, insprängda myrar och sjöar som bildar en komplex landskapsmosaik.

Mätningar av hydrologi, klimat, vatten- och markvattenkemi har pågått i Krycklan i över 30 år.
Krycklans avrinningsområde
Keywords: GEOCHEMISTRY; SOILS; FOREST SCIENCE; FORESTS; PEATLANDS; RIPARIAN WETLANDS; PEATLANDS; RIPARIAN WETLANDS; FROZEN GROUND; SEASONALLY FROZEN GROUND; TERRESTRIAL HYDROSPHERE; WATER QUALITY/WATER CHEMISTRY; TOTAL RUNOFF; DISCHARGE/FLOW; RIVERS/STREAMS; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap